2021
DOI: 10.1016/s2213-2600(21)00164-8
|View full text |Cite
|
Sign up to set email alerts
|

Global, regional, and national burden of respiratory tract cancers and associated risk factors from 1990 to 2019: a systematic analysis for the Global Burden of Disease Study 2019

Abstract: Background Prevention, control, and treatment of respiratory tract cancers are important steps towards achieving target 3.4 of the UN Sustainable Development Goals (SDGs)-a one-third reduction in premature mortality due to non-communicable diseases by 2030. We aimed to provide global, regional, and national estimates of the burden of tracheal, bronchus, and lung cancer and larynx cancer and their attributable risks from 1990 to 2019.Methods Based on the Global Burden of Diseases, Injuries, and Risk Factors Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(72 citation statements)
references
References 51 publications
1
69
0
2
Order By: Relevance
“…In the present study, we evaluated the real-world population data of regional registries on a global scale, revealing the global patterns and trends in incidence and mortality of TBL cancer. We found that 1 a substantial number of countries with very high HDI had higher incidence and mortality ASRs in both men and women than other countries 2 ; decreasing trends in mortality were found in the males of almost all countries, whereas females of nearly half of the countries had an increasing trend in mortality 3 ; decreasing trends in incidence were found among males of the majority of countries, especially for men younger than 50 years old 4 ; females of most countries were identified to have an increasing trend in incidence, while females younger than 50 years exhibited a quite opposite trend.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…In the present study, we evaluated the real-world population data of regional registries on a global scale, revealing the global patterns and trends in incidence and mortality of TBL cancer. We found that 1 a substantial number of countries with very high HDI had higher incidence and mortality ASRs in both men and women than other countries 2 ; decreasing trends in mortality were found in the males of almost all countries, whereas females of nearly half of the countries had an increasing trend in mortality 3 ; decreasing trends in incidence were found among males of the majority of countries, especially for men younger than 50 years old 4 ; females of most countries were identified to have an increasing trend in incidence, while females younger than 50 years exhibited a quite opposite trend.…”
Section: Discussionmentioning
confidence: 60%
“… 1 A recent study has revealed that smoking is still the primary risk factor for TBL cancer, and other risk factors include air pollution, exposure to asbestos and high fasting plasma glucose. 2 , 3 The survival rate of TBL cancer is relatively poor and it is still regarded as a substantial public health burden. 4 And early screening has a great potential for decreasing the mortality of tracheal, bronchus, and lung cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lung cancer is one of the most malignant cancers with high morbidity and mortality rate for both men and women in the world. Non-small cell lung cancer (NSCLC) is one subtype of lung cancer, which accounts for 85% of all the lung cancers (1). Although lung cancer has not been associated historically with abnormalities of the central neural system, an increasing body of evidence suggests that patients with lung cancer may be associated with neurocognitive impairments (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is a deadly disease with more than 10 million new cases each year 1 due to low specificity, poor solubility, poor bioavailability, multi-drug resistance, low therapeutic results, and high cytotoxicity of conventional chemotherapeutic medication. 2 Prostate, lungs, 3 stomach, 4 and colorectal cancer 5 are different and the most common types of cancer.…”
Section: Introductionmentioning
confidence: 99%